ANALISIS KEPERCAYAAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN SERTA IMPLIKASINYA TERHADAP LOYALITAS PASIEN DI RSUD DR. FAUZIAH BIREUEN - ACEH - Nirwansyah, Nirwansyah; Yanna, Sri; Afriana, Afriana (LPPM-UNIKI, 2026)
Patient loyalty analysis at a hospital must be continuously monitored and optimal solutions sought. This is certainly related to patient satisfaction itself, which is influenced by both internal and external factors, such as patient trust in the hospital, the quality of service they perceive, or the experiences experienced by their families. Analysis using a statistical approach to prove the hypothesis, namely path model analysis between the variables studied. Data were collected through questionnaires from a sample of 325 outpatients at Dr. Fauziah Bireuen Regional Hospital. The results obtained: (1) There is a causality between patient trust and service quality of 0.656, which directly and indirectly influences patient satisfaction. Simultaneously, patient trust and service quality contribute positively to patient satisfaction by 58.1%. (2) The influence of patient trust on patient satisfaction, considering service quality, is 25.13%. And the direct and indirect influence of service quality on patient satisfaction, through patient trust, is 23.59%. (3) There is a direct and indirect influence of patient trust on patient loyalty, considering service quality, of 37.78%. And the influence of service quality on patient loyalty, through patient trust of 25.4%. (4) Simultaneously, patient trust and service quality make a positive contribution to patient loyalty of 64.3%.